Applying the sign luminance computation model to study the effects of other vehicles on sign luminance - Ye, Fan; Carlson, Paul J.; Brimley, Bradford K. (Transport, 2014)
As one external lighting source on the road, headlamps from adjacent vehicles in the stream traffic should not be ignored. No comprehensive study has yet been developed for exploring the influence of sign luminance produced by other vehicle headlamps. In this paper, a luminance calculation model is developed to calculate sign luminance from all potential headlamps in the stream traffic. Using the model, four main scenarios have been simulated to analyze the effects of the positions of the target vehicle and other vehicles, vehicle type, sign type and sheeting material on the sign luminance. In addition, occlusion between vehicles is also addressed in the paper, by calculating the minimum distances between vehicles for the headlamps and for the driver’s view of the following vehicle when vehicles and the sign are and are not in the same lane.